Penerapan Model Pembelajaran Mind Mapping untuk Meningkatkan Hasil Belajar Ilmu Pengetahuan Sosial Murid Kelas V SDN No.105 Inpres Pa’bundukang Kec. Pattallassang Kab. Takalar - Hastati, Sri; Asis, Abdul (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The main objective of this research is to improve the learning outcomes of Social Sciences through the application of the Mind Mapping learning model for the fifth grade students of SDN No. 105 Inpres Pa'bundukang Kab. Takalar. The subjects of this study were fifth grade students at SDN No. 105 Inpres Pa'bundukang with 15 students (10 men and 5 women). The implementation of this research is in the odd semester of the 2021/2022 academic year. The data collection technique used in this study is the test used to obtain data about student learning outcomes which were carried out at the last meeting in each cycle. The data analysis technique used in this study was analyzed using quantitative analysis based on student learning outcomes and qualitative data obtained based on observations of student learning activities and teacher teaching activities. The results showed that the student's interest in learning in the first cycle with the percentage of student learning outcomes classically was 67.5% and experienced an increase in learning outcomes in the second cycle with the percentage of student learning outcomes classically that was 70.6, resulting in an increase in student learning outcomes from the second cycle. I to cycle II.